RURAL RESIDENTIAL ARCHITECTURAL HERITAGE OF TORRES VEDRAS - Fernandes, Inês Pires (European Scientific Journal, ESJ, 2015)
The residential architectural heritage in rural areas – erudite or just for agricultural purposes – corresponds to a significant portion of the Portuguese built heritage. Region’s economic centers, in the past, due to its agricultural potential, agricultural farms and suburban villas (known as Quinta de Recreio), given their eccentricity to the cultural and touristic city centers, are nowadays abandoned and ignored, with regard to dissemination and tourism exploitation. The aim of this paper is to present the architectural values and the potential of these buildings. The amount of these types of properties along the Southeast zone of Torres Vedras proves their economic and cultural importance for the region. These properties structure even nowadays, the villages and the rural area of Torres Vedras, marking and segmenting the agricultural fields. Their agricultural, hydraulic and recreational structures spread throughout the country and become the characteristic landscape of this special region. Despite its importance for the economy, the employability and for rural development, its current abandonment, the lack of information and safeguard programs, undertake the knowledge of this important part of history. Therefore, it is proposed their rehabilitation and the creation of a tourist and recognition route.